The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1108/jima-06-2020-0190
|View full text |Cite
|
Sign up to set email alerts
|

Customer participation, value co-creation and customer loyalty: evidence from Umrah travel agencies in Indonesia

Abstract: Purpose This study aims to elucidate customer participation and value co-creation in enhancing customer loyalty in the context of Umrah travelers. First, it identifies the antecedents of Umrah travelers’ participation including service brand image, service employee performance and willingness to customize. Second, this study explores the impact of Umrah travelers’ participation in Umrah travelers’ loyalty. Finally, it explores co-creation value (hedonic, refreshment and price) and Umrah travelers’ satisfaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 89 publications
(112 reference statements)
5
18
0
1
Order By: Relevance
“…The results have revealed that there are positive associations between university image and the dimensions of participation behavior such as information seeking, information sharing, personal interaction, and responsible behavior. This study's outcomes complement the findings of Mursid & Wu (2021) that institutional image positively influences the customers' participation (such as that of HEIs on student participation). Thus, HEIs having a sound image can ultimately encourage international students to interact openly and enhance the latter's information exchange and spontaneous participation behaviors with their personnel or staff.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The results have revealed that there are positive associations between university image and the dimensions of participation behavior such as information seeking, information sharing, personal interaction, and responsible behavior. This study's outcomes complement the findings of Mursid & Wu (2021) that institutional image positively influences the customers' participation (such as that of HEIs on student participation). Thus, HEIs having a sound image can ultimately encourage international students to interact openly and enhance the latter's information exchange and spontaneous participation behaviors with their personnel or staff.…”
Section: Discussionsupporting
confidence: 74%
“…According to Mursid & Wu (2021), customer participation is significantly influenced by the image of the institutional services.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…CPB, an essential element for the service sector, is considered one of the crucial factors affecting firm performance (Ngo and O'Cass, 2013). It is an essential determinant of customer loyalty (Eisingerich and Bell, 2006;Auh et al, 2007), customer satisfaction (Mursid and Wu, 2021;Yi et al, 2021), perceived service quality (Wang et al, 2007;Dong et al, 2008), repurchase intention (Chen and Wang, 2016), brand loyalty and brand satisfaction (Solem, 2016;Nardi et al, 2020). Therefore, customer participation is considered an essential factor affecting the firm's success.…”
Section: Structural Model Resultsmentioning
confidence: 99%
“…It is an essential determinant of customer loyalty ( Eisingerich and Bell, 2006 ; Auh et al. , 2007 ), customer satisfaction ( Mursid and Wu, 2021 ; Yi et al. , 2021 ), perceived service quality ( Wang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple research studies (Sibarani & Maximillian, 2021) have illustrated that the customers are found to be highly attracted towards brands due to effective marketing communication strategies adapted by the companies to attract their clients in this competitive environment. They argue that the marketing communication strategies have been found as a good source of building, nurturing and maintaining strong relationships with their customers (Mursid & Wu, 2021). The study illustrates when the customers have gone through these promotional campaigns, they develop expectations from these promoted brands and try to acquire them to satisfy their needs.…”
Section: Relationship Between Marketing Communication and Customer Loyaltymentioning
confidence: 94%